Cytotoxicity, antihypertensive, antidiabetic and antioxidant activities of solid-state fermented lupin, quinoa and wheat by Bifidobacterium species: In-vitro investigations. (September 2018) - Ayyash, Mutamed; Johnson, Stuart K.; Liu, Shao-Quan; Al-Mheiri, Aysha; Abushelaibi, Aisha
Abstract: This study aimed to investigate the in-vitro cytotoxicity activity against two cancer cell lines, α-amylase and α-glucosidase inhibitions, ACE-inhibition, antioxidant and proteolytic activities of whole-grain lupin, quinoa and wheat fermented by three species of Bifidobacterium spp. B. animalis, B. breve and B. longum were employed in solid-state fermentation (SSF) 37 °C for 72 h. The ranges of total phenolic contents in fermented lupin (FL), quinoa (FQ) and wheat (FW) were ∼17.0 to 44.0, ∼11.0 to 36.0, ∼5.0–29.0 mg GAE/g, respectively, relative to the unfermented control. α-Glucosidase inhibition increased significantly ( p  < 0.05) in FL and FQ after 24 h of fermentation. The cereals fermented by B. breve and B. longum had markedly increased ACE-inhibition activities. The magnitude of the cytotoxicity activities in FL was greater ( p  < 0.05) by approximately 5-fold and 3-fold against colon cancer cell (Caco-2) and breast cancer cell (MCF-7), respectively than in FQ and FW. The findings suggest that health properties of grains could be enhanced by probiotic fermentation and such enhancements depend on grain type and probiotic species. The inclusion of grains fermented by probiotics into foods could improve health benefits of these product. Highlights: Fermented cereal possessed greater anticancer and antihypertensive activities. Cereals fermented by Bifidobacterium spp had noticeable health benefits. Fermented cereals showed excellent antidiabetic activities.